Chromium Poisoning of La1-xSrxMnO3±δ Cathodes and Electrochemical Validation of Chromium Getters in Intermediate Temperature-Solid Oxide Fuel Cells. Issue 13 (1st January 2019) - Heo, Su Jeong; Hong, Junsung; Aphale, Ashish; Hu, Boxun; Singh, Prabhakar
Abstract : The effect of chromium poisoning on electrochemical performance degradation has been studied at intermediate temperatures (550–650°C) using La1-x Srx MnO3±δ (LSM) cathode and an electrochemical cell configuration air/LSM//YSZ//Pt/air. A rapid increase in polarization resistance is observed in the presence of gaseous chromium species containing humid air (3% H2 O) at both 550°C and 650°C. Cross-sectional elemental mapping and high-resolution transmission electron microscopy of the LSM/YSZ interface show the presence of crystalline Cr2 O3 and (Mn, Cr)3 O4  phases indicating reduction of gaseous hexavalent-chromium species and deposition of solid reaction products. Subsequent experiments, performed under the above exposure conditions but in the presence of a chromium getter, showed stable polarization resistance. The electrochemical performance of half-cells in Cr-containing humid air atmosphere and in the presence of the chromium getter also remained stable during 100-h tests at 550 and 650°C, respectively. The post-test structural and chemical analysis of the electrode, electrode-electrolyte interface and getter by scanning- transmission electron microscopy, energy dispersive X-ray and Raman spectroscopy showed that the cathode bulk and cathode- electrolyte interface remained free of chromium deposits whereas chromium species deposited near the air inlet region of the porous getter as crystalline SrCrO4 .